2007
DOI: 10.1007/s00068-007-7094-5
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Proximal Humeral Fractures with an Intramedullary Nail: Tipps and Tricks

Abstract: Antegrade interlocking nailing has been established as a valid option of treatment in proximal humeral fractures which follows the principles of minimum invasive surgery. The introduction of angular stability into intramedullary nailing has increased the stability of reconstruction even in osteoporotic fractures. The outcome of the surgical procedure essentially depends on the adequate intraoperative management of the specific features and challenges of the corresponding fracture type. The creation of the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Two devices have been introduced to treat displaced proximal humeral fractures: an antegrade angular stable intramedullary nail [26,32,33] and an angular stable plate [13,18,22]. Both devices are intended to achieve maximum primary angular stability by three-dimensionally arranged interlocking screws at the humeral head level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two devices have been introduced to treat displaced proximal humeral fractures: an antegrade angular stable intramedullary nail [26,32,33] and an angular stable plate [13,18,22]. Both devices are intended to achieve maximum primary angular stability by three-dimensionally arranged interlocking screws at the humeral head level.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently applied methods to treat displaced proximal humeral fractures include minimally invasive techniques with Kirschner wires/sutures and/or screw fixation, plate fixation, intramedullary interlocking nailing, and hemiarthroplasty. The choice of surgical technique depends on the fracture type and the patient's age, bone quality, and functional expectation [2,12,13,22,29,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Authors concluded that to prevent mobilization and improve results, nail and screws must be applied in the regions with the highest trabecular density (22). Other studies confirmed that there is a lower risk of mobilization, as well as correct positioning of the nail, when the proximal screws reach within few mm of the epiphyseal cortex (17,20,22,23), owing to the higher bone density of this subchondral bone area. However, this is also a risk because screws may protrude into the joint, causing joint damage and functional impediment.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors recommend surgery with an endomedullary nail as the treatment of choice in displaced fractures with two or three fragments according to Neer's classification, in that it is a good compromise between minimally invasive treatment and the insertion of a plate, reserved for younger patients. The literature contains reports of endomedullary nailing with proximal screw locking [1,2,5,7,8] or wires [4,6]. Proximal humerus nailing, used in our cases and mentioned in recent literature [9][10][11][12], has a proximal locking mechanism with a spiral blade.…”
Section: Introductionmentioning
confidence: 93%